A HOMER-Aided Study for PV System Design and Cost Analysis for a College Campus in Baghdad - Luqman Q. Ibrahim; Ahmed J. Abid; Adel A. Obed; Ameer L. Saleh; Reheel J. Hassoon (Journal of Techniques)
Due to the lack of electric power generation in Iraq and as a step forward to adopting a sustainable campus of the Electrical Engineering Technical College (EETC), Middle Technical University, in Baghdad, Iraq, and the critical demand for energy in our institutions, particularly educational institutions, this pilot study was proposed. The study aims to analyze the adoption of PV solar systems on the campus in the presence and absence of grid power and how that affects our design discussion in the matter of Net Present Cost (NPC), Cost of Energy (COE), Operation Cost, initial cost, power production, fuel consumption, and the annual net consumed energy from the grid. Forty-five different scenarios were analyzed for all possible cases. The existence of backup generators on the campus was also taken into consideration; G1-350kVA and G2-500kVA. The study has two stages. In the first stage, they used a walkthrough energy audit in the (EETC) to estimate the load profile of the campus, while in the second stage, they used HOMER Pro to analyze this data. The results show that adding an on-grid PV system to the campus grid can reduce the COE by 58%, and it is the best scenario when the grid is present, with an NPC, operation cost ($/yr), and initial capital ($) equal to $77,680, $1,460, and $59,018 respectively. When the grid was absent, the winning scenario was using a PV solar system with a 100-kWh lithium battery storage and a converter. Despite that scenario being the best solution, the produced energy cost is 372% higher than the grid energy cost (0.1 $/kWh) in Iraq, with an NPC, operation cost ($/yr.), and initial capital ($) equal to $337,291, $7,855, and 236878 respectively. Finally, both winning scenarios have no generator, and this will have a high impact on the campus environment.